1997
DOI: 10.1093/oxfordjournals.molbev.a025727
|View full text |Cite
|
Sign up to set email alerts
|

RFLP markers show genetic recombination in Botryotinia fuckeliana (Botrytis cinerea) and transposable elements reveal two sympatric species

Abstract: Molecular markers revealed that Botryotinia fuckeliana (the teleomorph of Botrytis cinerea), a haploid, filamentous, heterothallic ascomycete, contained a large amount of intrapopulation genetic variation. The markers were used to determine the mode of reproduction and the population structure of this fungus. We did not detect any differentiation between isolates from different organs, collection dates, varieties of grape, or locations in the Champagne region of France, but two unexpected sympatric populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
130
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(171 citation statements)
references
References 32 publications
(27 reference statements)
12
130
0
9
Order By: Relevance
“…1 and 2). In combination with previous genetic studies, this suggests that B. cinerea is not reproducing in a clonal manner and, instead, is allowing for extensive recombination from either meiotic or mitotic processes to generate a large pool of diversity (Amselem et al 2011;Fournier and Giraud 2008;Fournier et al 2002;Giraud et al 1997Giraud et al , 1999Ma and Michailides 2005;Munoz et al 2002;Rowe and Kliebenstein 2007;Staats and van Kan 2012). This genetic diversity and its phenotypic consequences among the isolates could be what allows B. cinerea to infect such a large number of potential plant hosts.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1 and 2). In combination with previous genetic studies, this suggests that B. cinerea is not reproducing in a clonal manner and, instead, is allowing for extensive recombination from either meiotic or mitotic processes to generate a large pool of diversity (Amselem et al 2011;Fournier and Giraud 2008;Fournier et al 2002;Giraud et al 1997Giraud et al , 1999Ma and Michailides 2005;Munoz et al 2002;Rowe and Kliebenstein 2007;Staats and van Kan 2012). This genetic diversity and its phenotypic consequences among the isolates could be what allows B. cinerea to infect such a large number of potential plant hosts.…”
Section: Discussionmentioning
confidence: 79%
“…B. cinerea is a necrotrophic fungal plant pathogen with an extremely broad host range and is responsible for postharvest crop loss across the globe (Williamson et al 2007). Further, B. cinerea is known to have a large amount of standing genetic variation (Aguileta et al 2012;Alfonso et al 2000;Atwell et al 2015;Baraldi et al 2002;Fournier and Giraud 2008;Fournier et al 2002;Giraud et al 1997Giraud et al , 1999Ma and Michailides 2005;Munoz et al 2002;Rowe and Kliebenstein 2007;Staats and van Kan 2012). Several studies have shown that this genetic diversity within B. cinerea not only contributes to differential virulence in planta (Calpas et al 2006;Denby et al 2004;Rowe and Kliebenstein 2008;Schumacher et al 2012) but can also contribute to the development of fungicide resistant genotypes (Kretschmer et al 2009).…”
mentioning
confidence: 99%
“…Based on the presence or absence of the transposons Boty and Flipper in the genome, two sub-populations, transposa and vacuma, have been reported in B. cinerea (Giraud et al, 1997(Giraud et al, , 1999Levis et al, 1997). The transposable elements Boty and Flipper were described for the first time by Diolez et al (1995) and Levis et al (1997), respectively.…”
Section: Survival Inoculum Sources and Dispersalmentioning
confidence: 99%
“…The transposable elements Boty and Flipper were described for the first time by Diolez et al (1995) and Levis et al (1997), respectively. Transposa isolates carry Boty and Flipper, whereas both of these transposable elements are absent in vacuma isolates (Giraud et al, 1997). Isolates carrying either Boty or Flipper in the B. cinerea genome have also been described (De Miccolis Angelini et al, 2003;Giraud et al, 1999;Muñoz, et al, 2002).…”
Section: Survival Inoculum Sources and Dispersalmentioning
confidence: 99%
“…Transposons have been used to distinguish genetically divergent populations because they can mark specific genotypes that have a common ancestor (Dobinson et al, 1993;Giraud et al, 1997;He et al, 1996;Kachroo et al, 1994;Mouyna et al, 1996;Shull and Hamer, 1996;Zhu and Oudemans, 2000). In F. oxysporum f. sp.…”
Section: Transposable Elements As Genetic Tools: Gene Isolation and Amentioning
confidence: 99%